Quantification of Main Bcr-abl Gene Transcripts in CML Patients Using Competitive RT-PCR - Ali Nazemi; Mehrdad Hashemi; Shahrashoub Sharifi; Abolfazl Movafagh (Asian Pacific Journal of Cancer Biology, 2016)
Chronic myelogenous leukemia (CML) is the outcome of a chromosomal translocation and abl and bcr genes fusion. The present study is an attempt to implement a simple and inexpensive method for quantification of bcr-abl fusion transcripts in CML patients. Competitive RT-PCR technique was used to quantify bcr-abl transcripts. Internal control DNA piece was designed and synthesized from a non-human source, which was smaller than the target DNA in length but with the end identical to the main target piece. Following proliferation and purification, the transcriptions were quantified. To optimize reaction condition, competitive PCR was first performed separately on the target DNA with a given number of copies and a given number of copies of internal controls and the result of the reaction was electrophoresed for all concentrations of agarose electrophoreses gel. Results of simultaneous reactions of target RNA along with different number of copies of internal controls showed that the number of target RNA copies can e determined through comparing intensity of the color of DNA bands on the gel. The results showed that comparing with other methods like Real-time, the competitive RT-PCR is a relatively efficient and economic method to quantify bcr-abl transcripts.